Application of the environmental pillar within the world-class manufacturing methodology for the purpose of achieving environmental sustainability - Amer Abdul Latif Kadhum; Bilal Ahmed Hassan (International Journal of Production Management and Engineering)
Environmental sustainability is one of the main dimensions involved in achieving sustainable industrialization through the application of practices reduction the consumption of environmental resources, and reduce the volume of waste and emissions, so the study aims to apply the environmental pillar associated with the methodology of (World Class Manufacturing – WCM) in one of the Iraqi manufacturing organizations for the purpose of achieving its environmental sustainability. The study site lacks knowledge of modern scientific theories related to these practices. The results of the study indicate that there are a number of gaps in the application of environmental procedures within the study site, and the extent of compliance with them, and the study concludes that the success of achieving environmental sustainability depends on the extent of commitment to achieve the study proposals, the most prominent of which were internal environmental goals, the application of the environmental training program, the extent of application of energy management standards, as well as the conformity of the international standard (ISO 14001 2015) of the Environmental Management System.